Musnad ʿAbd Allāh ibn al-Zubayr al-Ḥumaydī as an Early Source of Madanī isnād: A Source Critical Study - Gaafar, Heba Mohamed (AUC Knowledge Fountain, 2025)
The transmission of ḥadīth has been a subject of intense debate, particularly regarding the authenticity of early compilations. Musnad al-Ḥumaydī is a ḥadīth collection that has not received significant scholarly attention despite its potential to shed light on early ḥadīth transmission. This study critically examines Musnad al-Ḥumaydī by analyzing its structure, sources, and methodology, focusing on its relationship with Sufyān b. ʿUyayna, the primary transmitter of its ḥadīth. By applying isnād analysis and source criticism, this research challenges the assumption that early ḥadīth compilations were unreliable or retrospectively constructed. Al-Ḥumaydī did not simply collect narrations. The study demonstrates that Musnad al-Ḥumaydī reflects a structured and systematic approach to ḥadīth preservation, offering valuable insights into early Islamic scholarship, legal traditions, and the role of Madanī isnād. The findings contribute to the ongoing reassessment of ḥadīth authenticity and provide a more nuanced understanding of how the Sunnah was transmitted and documented in the early centuries of Islam.